Evaluasi Usability pada Situs Web Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sidoarjo menggunakan Metode Heuristic Evaluation - Muhammad Zakhy Fitra Gusri; Buce Trias Hanggara; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The website of the Agency of Population and Civil Registration of Sidoarjo Regency is a service portal owned by the Sidoarjo Regency Government which aims to provide online-based services to the people of Sidoarjo. In accordance with Regent Regulation No. 46 of 2018, there is a need for a guarantee of service quality and an increase in the quality of online-based services from every field of government in Sidoarjo Regency. So it is necessary to evaluate the service tools belonging to the Sidoarjo Regency Government to be able to continue to improve the quality of their services, one of them is the website of the Sidoarjo Regency Population and Civil Registration Service, which is located at www.disdukcapil.sidoarjokab.go.id. This study aims to find usability problems from the website and provide recommendations for improvements to the findings of these problems. This study uses the Heuristic Evaluation method in evaluating the website by involving 3 experts in the UI / UX field. From the evaluation results found 19 heuristic problems which are divided into 2 cosmetic problems, 2 minor problems, 2 major problems, and 13 catastrophic problems. From the findings of these problems, recommendations for improvement were given in the form of a visual user interface design of 5 web page designs with 19 recommendations for improvement.